Application of mitochondrial pyruvate carrier blocker UK5099 creates metabolic reprogram and greater stem-like properties in LnCap prostate cancer cells in vitro - Zhong, Yali (Oncotarget, 2015)
Aerobic glycolysis is one of the important hallmarks of cancer cells and eukaryotic cells. In this study, we have investigated the relationship between blocking mitochondrial pyruvate carrier (MPC) with UK5099 and the metabolic alteration as well as stemness phenotype of prostatic cancer cells. It was found that blocking pyruvate transportation into mitochondrial attenuated mitochondrial oxidative phosphorylation (OXPHOS) and increased glycolysis. The UK5099 treated cells showed significantly higher proportion of side population (SP) fraction and expressed higher levels of stemness markers Oct3/4 and Nanog. Chemosensitivity examinations revealed that the UK5099 treated cells became more resistant to chemotherapy compared to the non-treated cells. These results demonstrate probably an intimate connection between metabolic reprogram and stem-like phenotype of LnCap cells in vitro. We propose that MPC blocker (UK5099) application may be an ideal model for Warburg effect studies, since it attenuates mitochondrial OXPHOS and increases aerobic glycolysis, a phenomenon typically reflected in the Warburg effect. We conclude that impaired mitochondrial OXPHOS and upregulated glycolysis are related with stem-like phenotype shift in prostatic cancer cells.